The Production of Porous Aluminum Hydroxide Using Aluminum Nanopowder; Modern Techniques and Technoloqies MTT' 2005 - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Ilyin A. P. Aleksandr Petrovich; An V. V. Vladimir Vilorievich; Astankova A. P. Anna Petrovna (2005, 2005)
Aluminum hydroxide is made good use of production of ceramic materials, is applied to catalytic agent production, and is also widespread technical adsorbent, filling material of polymer and others. The application productivity of aluminum hydroxide is depends on method of its production and type of source material. These substances are usually produced with hydrolysis of aluminum salts, with sedimentation from aqueous solution of aluminum nitrate by ammonium hydroxide (sol-gel method), with chamber sedimentation using sulphate process, with method of selective oxidation from gallium-aluminum alloy, and with hydrothermal synthesis. The last method is remarkable for relatively simplicity and productivity in order to obtain aluminum hydroxides, which could has a developed surface of particles.